Pengembangan Media Ropuca untuk Pembelajaran Bahasa Indonesia Kelas 1 Sekolah Dasar - Zuhirotunnisa Zuhirotunnisa; Dina Saputri Dewi; Abelia Riski Ramadhani (STIKes Ibnu Sina Ajibarang, 2025)
This study aims to develop ROPUCA (Roda Putar dan Papan Baca) learning media in teaching vowels and consonants. This media is designed to create an interactive and enjoyable learning experience in building early reading skills. This study uses the Research and Development (R&D) method with the ADDIE development model, which consists of five stages: analysis, design, development, implementation, and evaluation. The validation results show a percentage of 100% from material experts, 81% from media experts, and 100% from field practitioners. Individual trials obtained results of 92%, small group trials 100%, and field trials reached 91%. The data obtained show that ROPUCA media contributes to helping students recognize consonants and vowels and understand the basics of reading more effectively. This media is used in learning for grade I elementary school students.